2016
DOI: 10.22456/1679-9216.81082
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Feed Supplement in Advanced Stages of Feline Chronic Kidney Disease

Abstract: Background: Chronic kidney disease (CKD) is a very common pathology in cats, especially in the geriatric age. A proper renal diet is considered the current standard of care to enhance patients’ long-term survival and quality of life. However, when diet alone is not sufficient, it is necessary to supplement it with specific substances: these are phosphate binders and alkalinizing agents. The aim of this study was to evaluate the effectiveness of a feed supplement containing calcium carbonate, calcium lactate gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(34 reference statements)
0
2
0
1
Order By: Relevance
“…Mit zunehmender Schwere der Nierenerkrankung sinkt die Fähigkeit der Niere, Phosphat auszuscheiden, und dies muss bei der Therapie berücksichtigt werden 1 , 4 . Phosphat spielt nach aktuellem Wissensstand eine essenzielle Rolle bei der Bemühung, die Progression einer CNE zu verlangsamen 5 . Die Menge des über das Futter aufgenommenen Phosphates korreliert mit der Morbidität und Mortalität 6 , 7 .…”
Section: Therapie Der Begleiterkrankungenunclassified
“…Mit zunehmender Schwere der Nierenerkrankung sinkt die Fähigkeit der Niere, Phosphat auszuscheiden, und dies muss bei der Therapie berücksichtigt werden 1 , 4 . Phosphat spielt nach aktuellem Wissensstand eine essenzielle Rolle bei der Bemühung, die Progression einer CNE zu verlangsamen 5 . Die Menge des über das Futter aufgenommenen Phosphates korreliert mit der Morbidität und Mortalität 6 , 7 .…”
Section: Therapie Der Begleiterkrankungenunclassified
“…Therefore, early detection and diagnosis can provide basis for timely treatment, alleviate clinical symptoms, delay the progress of the disease and reduce the occurrence of death, which is of great significance to CKD patients [6]. Galectin -3(Gal-3) can promote angiogenesis, change the morphology of vascular endothelial cells, improve microvascular lesions caused by CKD, and can be used as the main index to observe the condition of patients with CKD complicated with chronic kidney disease [7]. Klotho protein is a co-receptor of FGF23, which is mainly expressed in the distal tubule of kidney.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Cats, especially of geriatric age, are commonly affected by CKD. 3,4 In human medicine, it has been shown that oxidative stress (OS) is associated with uraemia. 5 It has been hypothesised that two main events occur in CKD: the facilitation of inflammation and OS by uraemic toxins, 6 and the impairment of antioxidant enzymes in uraemia.…”
Section: Introductionmentioning
confidence: 99%